Sensibilidad antimicrobiana a Escherichia coli aislada de pacientes con infección tracto urinario en el Hospital de Apoyo de Chepén - Antinori Castro, Roxana Maribel (2020)
The objective of this quantitative, descriptive, cross-sectional and retrospective investigation was to determine the antimicrobial sensitivity of Escherichia coli isolated from patients with urinary tract infection treated at the Chepén Support Hospital, during the months of January-June, 2018. The population was made up of 205 medical records. Microbiology record book data was collected, then in the statistics office they were corroborated with the medical records, which were entered and processed in the Excel program. The best sensitivity results for Escherichia coli were represented by cefoxitin (92.9%), amikacin (90.7%); nitrofurantoin (87%) ceftriaxone (84.3%) and ampicillin (28.6%), nadilixic acid (29.3) amoxicillin / ac. Clávulamico (34.9%) are the ones that present less sensitivity. The sensitivity study by family of antibiotics shows that the highest percentage of sensitivity is for carbapenemases (92.1%), followed by nitrofurans (88.5%) and monobactams (83.7%); being penicillins (28.6%) that present a lower percentage of sensitivity.